Challenges and Opportunities for Labor Absorption: Case Study in West Java Province through Panel Data Approach - Rahmayani, Rizka (CV. Strata Persada Academia, 2024)
Despite having a relatively high economic growth rate, West Java Province still faces severe challenges in labor absorption, as reflected by the high Open Unemployment Rate (OUR). This study aims to analyze the effect of Gross Regional Domestic Product (GRDP), investment, and minimum wages on OUR in West Java Province during 2018-2022. This study uses a panel data approach by combining time series and cross-sectional data from several districts/cities in West Java. The data were analyzed using the panel data regression method with a fixed effect model (FEM) selected based on the results of the Hausman test. The results showed that GRDP had a negative and significant effect on OUR, indicating that economic growth was correlated with a decrease in the unemployment rate. On the other hand, investment did not significantly affect OUR in West Java during the study period. Meanwhile, the minimum wage also did not significantly affect. This study recommends encouraging inclusive economic growth, especially in labor-intensive sectors, and directing investment policies to create quality jobs. Training programs and workforce skills must also be improved to suit industry needs.